The Participation of Cadres with the compliance of toddlers visits to the Integrated Healthcare Center - Riza Tsalatsatul Mufida; Miftakhur Rohmah; Retno Palupi Yonni Siwi; Mila Karmila (Universitas STRADA Indonesia, 2023)
Peer Health development can function optimally if it is supported by community empowerment and as a form of community empowerment is the presence of Integrated Healthcare Center cadres and mothers of toddlers who bring their toddlers to Integrated Healthcare Center. The purpose of this study was to analyze the relationship between the participation of Integrated Healthcare Center cadres with the compliance of toddlers' visits to the Integrated Healthcare Center at the Sejahtera Integrated Healthcare Center. This study uses a correlational analytic design with a cross sectional approach. The sample in this study were 32 respondents with a total sample of 35 respondents. sampling in this study using simple random sampling technique. Collecting data using questionnaires and MCH handbooks. Data analysis to see the relationship between the independent variable and the dependent variable using the chi square statistical test with a significant level of = 0.05. The results showed that from 32 respondents, most of the roles of Integrated Healthcare Center cadres were good, as many as 18 respondents (56.2%), and most of the respondents at the Sejahtera Integrated Healthcare Center, obediently visited the Integrated Healthcare Center, as many as 22 respondents (68 ,8%). The results of data analysis using Chi Square statistical test obtained P value < 0.05 (0.000 < 0.05) which means that there is a relationship between Integrated Healthcare Center cadre partk[icipation and compliance with toddler visits in Integrated Healthcare Center Sejahtera. The Integrated Healthcare Center activities can take place and there is an increase in visits by mothers of children under five to the Integrated Healthcare Center every month.